2018
DOI: 10.1016/j.ajpath.2018.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the Hajdu-Cheney Syndrome Mutation in CD19 B Cells in Mice Alters B-Cell Allocation but Not Skeletal Homeostasis

Abstract: Mice harboring Notch2 mutations replicating Hajdu-Cheney syndrome (Notch2) have osteopenia and exhibit an increase in splenic marginal zone B cells with a decrease in follicular B cells. Whether the altered B-cell allocation is responsible for the osteopenia of Notch2 mutants is unknown. To determine the effect of NOTCH2 activation in B cells on splenic B-cell allocation and skeletal phenotype, a conditional-by-inversion (COIN) Hajdu-Cheney syndrome allele of Notch2 (Notch2) was used. Cre recombination generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…This phenotypic difference in HCS compared to NICD1 overexpression can be a result of a constitutively active Notch2 receptor in HCS mice and also due to differences in expression and function of different Notch receptors. An inducible COIN by inversion model for HCS is available, and these will provide a better comparison with our inducible Notch1 findings 31,32 . In line with our data is recent work by Youngstrom et al 17 showing that local delivery of Notch ligand Jagged‐1 at the time of injury promotes regeneration of femoral and calvarial defects in mice and rats, with more physiological tissue formation than what was achieved with BMP2.…”
Section: Discussionsupporting
confidence: 85%
“…This phenotypic difference in HCS compared to NICD1 overexpression can be a result of a constitutively active Notch2 receptor in HCS mice and also due to differences in expression and function of different Notch receptors. An inducible COIN by inversion model for HCS is available, and these will provide a better comparison with our inducible Notch1 findings 31,32 . In line with our data is recent work by Youngstrom et al 17 showing that local delivery of Notch ligand Jagged‐1 at the time of injury promotes regeneration of femoral and calvarial defects in mice and rats, with more physiological tissue formation than what was achieved with BMP2.…”
Section: Discussionsupporting
confidence: 85%
“…Notch2 is required for the development of the marginal zone of the spleen, and mouse models of HCS exhibit a reallocation of marginal zone B cells at the expense of follicular cells but do not appear to develop marginal zone lymphomas [50, 51]. The reallocation of marginal zone B cells does not influence skeletal remodeling.…”
Section: Notch and Congenital Disorders Of The Skeletonmentioning
confidence: 99%
“…It is of interest that somatic NOTCH2 mutations causing loss of the PEST domain exhibit enhanced Notch2 activation and have been identified in B cell lymphoma, specifically in marginal zone B lymphoma of the spleen [49]. Notch2 is required for the development of the marginal zone of the spleen, and mouse models of HCS exhibit a reallocation of marginal zone B cells at the expense of follicular cells but do not appear to develop marginal zone lymphomas [50, 51]. The reallocation of marginal zone B cells does not influence skeletal remodeling.…”
Section: Notch and Congenital Disorders Of The Skeletonmentioning
confidence: 99%
“…Recently, we demonstrated that Notch2 tm1.1Ecan mice display splenomegaly and reallocation of marginal zone B-cells, but no evidence of T-cell abnormalities or of a generalized inflammatory process [28, 50]. These findings, coupled with the absence of macrophage infiltration in the synovium of sham- or DMM-operated Notch2 tm1.1Ecan mutants, suggest that NOTCH2 activation in joint tissues, and not in immune cells, drives osteoarthritis progression in Notch2 tm1.1Ecan mice.…”
Section: Discussionmentioning
confidence: 99%